The Gate to China : A New History of the People's Republic & Hong Kong - Sheridan, Michael, 1957- (London William Collins, 2021)
"A superb new history of the rise of China and the fall of Hong Kong to authoritarian rule. The rise of China and the fall of Hong Kong to authoritarian rule are told with unique insight in this new history by Michael Sheridan, drawing on eyewitness reporting over three decades, interviews with key figures and documents from archives in China and the West. The story sweeps the reader from the earliest days of trade through the Opium Wars of the 19th century to the age of globalisation and the handover of Hong Kong from Britain to China. It ends with the battle for democracy on the city's streets and the ultimate victory of the Chinese Communist Party. How did it come to this? We learn from private papers that Margaret Thatcher anguished over the fate of Hong Kong, sought secret American briefings on how to handle China and put her trust in an adviser who was torn between duty and pride. The deal they made with Beijing did not last. The Chinese side of this history, so often unheard, emerges from memoirs and documents, many new to the foreign reader, revealing how the party's iron will and negotiating tactics crushed its opponents. Yet the voices of Hong Kong people - eloquent, smart and bold - speak out here for ideals that refuse to die. Sheridan's book tells how Hong Kong opened the way for the People's Republic as it reformed its economy and changed the world, emerging to challenge the West with a new order that raises fundamental questions about progress, identity and freedom. It is critical reading for all who study, trade or deal with China"--Publisher's description.
Include Color Illustrations, Bibliography, Maps and Index
Keywords: China